Radio Frequency Transmission: Improving Radio Frequency Transmission Properties of Graphene via Carrier Concentration Control toward High Frequency Transmission Line Applications (Adv. Funct. Mater. 18/2019). (2nd May 2019) - Yang, Jae Hoon; Yang, Hyoung Woo; Jun, Byoung Ok; Shin, Jeong Hee; Kim, Seunguk; Jang, A‐Rang; Yoon, Seong In; Shin, Hyeon Suk; Park, Deoksoo; Park, Kyungho; Yoon, Duhee; Sohn, Jung Inn; et al.
Abstract : In article number1808057, Jae Eun Jang and co‐workers report an improvement in the radio frequency transmission properties of graphene via amorphous carbon deposition.